(untitled) (Islas, 2026)
Introduction: The Mexican Day of the Dead tradition exports representations of death internationally, associating it with imagery of skulls in colorful settings. In Brazil, contact with these elements is established through animations, films, and other references. However, little is known about calaveras literarias, a popular poetic manifestation that articulates social critique, humor, and death. This paper aims to translate and analyze a calavera literaria published in 1913, highlighting the challenges that its cultural and poetic specificity poses for its translation into Brazilian Portuguese. Methods: The primary method adopted is the commented translation of a poem. The methodological procedure comprises an analysis of the source text’s socio-historical context, the identification of culture-specific items, and translation decision-making guided by both the formal aspects of poetry (meter, rhyme, and rhythm) and issues of register and diachronic variation. The employed strategies are systematized through commentaries that link translation theory and practice. Results: The research produces a Portuguese translation that seeks to balance the preservation of poetic form and cultural meanings. The results demonstrate the need to negotiate losses and gains, as well as to adopt solutions that maintain the critical, humorous, and cultural dimensions of the calavera literaria in the target context. Conclusions: It is concluded that translating this genre demands careful attention to the relationships between language, culture, and identity, reinforcing the importance of methodological approaches that integrate textual and contextual analysis within Translation Studies.